2015
DOI: 10.1016/j.resuscitation.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Recreational drug overdose-related cardiac arrests: Break on through to the other side

Abstract: Introduction The annual rate of recreational overdose (OD)-related death is increasing exponentially, making unintentional overdose the leading cause of injury-related death in America. Unfortunately, little attention in the resuscitation community has focused on the post-arrest care of this rapidly growing population. Methods We included patients presenting between January 2009 and February 2014 after out-of-hospital cardiac arrest (OHCA) and abstracted baseline clinical characteristics and neurological out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…[11,12,13,35] When compared to the 2014 study by Koller et al and the 2016 study by Salcido et al , we found lower rates of survival among drug-related cardiac arrest patients (9.5% vs. 18.9% and 12.7% respectively). [11,12] In comparison with our findings, patient’s with opioid-related cardiac arrest in the Koller study had a much higher rate of witnessed arrests (48.4% vs. 27.5%) and initial shockable cardiac rhythms (15.6% vs. 7.78%).…”
Section: Discussionmentioning
confidence: 53%
“…[11,12,13,35] When compared to the 2014 study by Koller et al and the 2016 study by Salcido et al , we found lower rates of survival among drug-related cardiac arrest patients (9.5% vs. 18.9% and 12.7% respectively). [11,12] In comparison with our findings, patient’s with opioid-related cardiac arrest in the Koller study had a much higher rate of witnessed arrests (48.4% vs. 27.5%) and initial shockable cardiac rhythms (15.6% vs. 7.78%).…”
Section: Discussionmentioning
confidence: 53%
“…We were not able to find any publications looking at pre-treatment with Morphine and survival rate in animals after cardiac arrest. However, two recent retrospective studies demonstrated that patients who were treated with opioids before or during CA had a statistically significantly higher survival rate [37] and much better neurological outcome [38] compared to untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to find any publications looking at pre-treatment with Morphine and survival rate in animals after cardiac arrest. However, two recent retrospective studies demonstrated that patients who were treated with opioids before or during CA had a statistically significantly higher survival rate [36] and much better neurological outcome [37] compared to untreated patients.…”
Section: Discussionmentioning
confidence: 99%